Neonatal local noxious insult affects gene expression in the spinal dorsal horn of adult rats - Dubner Ronald; He Fang; Novikova Svetlana I; Ren Ke; Lidow Michael S (SAGE Publishing, 2005)
Abstract Neonatal noxious insult produces a long-term effect on pain processing in adults. Rats subjected to carrageenan (CAR) injection in one hindpaw within the sensitive period develop bilateral hypoalgesia as adults. In the same rats, inflammation of the hindpaw, which was the site of the neonatal injury, induces a localized enhanced hyperalgesia limited to this paw. To gain an insight into the long-term molecular changes involved in the above-described long-term nociceptive effects of neonatal noxious insult at the spinal level, we performed DNA microarray analysis (using microarrays containing oligo-probes for 205 genes encoding receptors and transporters for glutamate, GABA, and amine neurotransmitters, precursors and receptors for neuropeptides, and neurotrophins, cytokines and their receptors) to compare gene expression profiles in the lumbar spinal dorsal horn (LDH) of adult (P60) male rats that received neonatal CAR treatment within (at postnatal day 3; P3) and outside (at postnatal 12; P12) of the sensitive period. The data were obtained both without inflammation (at baseline) and during complete Freund's adjuvant induced inflammation of the neonatally injured paw. The observed changes were verified by real-time RT-PCR. This study revealed significant basal and inflammation-associated aberrations in the expression of multiple genes in the LDH of adult animals receiving CAR injection at P3 as compared to their expression levels in the LDH of animals receiving either no injections or CAR injection at P12. In particular, at baseline, twelve genes (representing GABA, serotonin, adenosine, neuropeptide Y, cholecystokinin, opioid, tachykinin and interleukin systems) were up-regulated in the bilateral LDH of the former animals. The baseline condition in these animals was also characterized by up-regulation of seven genes (encoding members of GABA, cholecystokinin, histamine, serotonin, and neurotensin systems) in the LDH ipsilateral to the neonatally-injured paw. The largest aberration in gene expression, however, was observed during inflammation of the neonatally injured hindpaws in the ipsilateral LDH, which included thirty-six genes (encoding numerous members of glutamate, serotonin, GABA, calcitonin gene-related peptide, neurotrophin, and interleukin systems). These findings suggest that changes in gene expression may be involved in the long-term nociceptive effects of neonatal noxious insult at the spinal level.